Expans\~ao de área agrícola no Brasil segundo as lavouras temporárias - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Food production remains one of the main challenges for humankind in this century, and Brazil is one of the main food-producing countries that have yet some land for economically or technically profitable farming expansion. Then, knowing which areas constitute the Brazilian agricultural frontier is crucial for improving public policies and logistics infrastructure decisions. Data from the Brazilian Institute of Geography and Statistics from 1995 to 2019 were used in this study. The study aimed to map and measure the expansion of agricultural areas in Brazil from 1995 to 2019 for temporary crops according to their mesoregions. The study used a four-stage methodology, compared the results of two agglomerative clustering methods, and identified similar mesoregions based on their share trends in the Brazilian agricultural seeded area. Some mesoregions had higher positive trend values for their share of the Brazilian agricultural seeded area: mato-grossense north (MT), mato-grossense northeast (MT), Mato Grosso do Sul southwest (MS), goiano south (GO), Bahia extreme west (BA), maranhense south (MA), piauiense southwest (PI), and Tocantins eastern (TO). As a second leading group, the Paranaíba Upstream (MG), S\~ao José do Rio Preto (SP), mato-grossense southeast (MT), and goiano east (GO), must be emphasized. Further research is recommended, including extending the study to permanent crops and applying top-down analysis targeting microregions or municipalities in the identified mesoregions.
Keywords: Q10; Q15; 330; agricultural frontier; Brazil; mesoregions; Spearman's correlation coefficient; clustering